PERLINDUNGAN HUKUM BAGI MASYARAKAT PENYANDANG DISABILITAS DI SLB NEGERI AUTIS SUMATERA UTARA - Siregar, Dahris; Darma, Mospa; Salsabilla, Khairani; Buulolo, Kadimani; Khairunnisa, Jihani; Ginting, Rani Salbiani (Jurnal Abdi Insani, 2024)
Harmonization of laws is very important in terms of the defence of individuals with disabilities as they are a cross-sectoral problem that affects many areas, including education, economics, politics, law, and so on. There is new hope for the rights under the law the those who are disabled possess that Law No. 8/2016 has ignored. In spite of this, people with disabilities still faced discrimination as legal subjects. Increasing public awareness of the rights guaranteed by laws and regulations is the aim of this service programme, and encourage persons with disabilities to support and defend their rights. One of the ways that the government hopes to implement the objectives of Law Number 8 of 2016 is by increasing accessibility. In SLB Negeri Autis North Sumatra, lecturers and students carried out this community service for one day through legal advice for the defence of disabled individuals. Participant motivation to it is anticipated that this move would spark a larger advocacy effort supporting the rights of people with impairments. They should also encourage neighbourhood organisations that assist people with impairments in leading fair, self-sufficient and inclusive lives.